Blue Light Exposure Duration Improves Antioxidant Capacity in Mung Bean Seedlings (Vigna radiata L.) - Kaylee Ann Siswanto; Artadana Made Ida Bagus (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Antioxidant chemicals found in mung bean (Vigna radiata L.) sprouts may help prevent non-communicable diseases linked to oxidative stress; however, it is unknown how long exposure to blue light affects the build-up of these bioactive substances. This study aimed to evaluate the effect of different duration of blue LED light exposure on growth, antioxidant activity, and antioxidant-related compound in mung bean sprout. Three replications of a completely randomized design (CRD) were used. The Folin-Ciocalteu method was used to measure total phenolic content, iodometric titration was used to measure vitamin C, and the DPPH assay was used to measure antioxidant activity. According to the results, antioxidant activity increased significantly (p<0.05) under 24-hour exposure to blue light (30.34±0.61%) compared to darkness (26.40±0.39%). Additionally, tests made using the Folin-Ciocalteu technique and iodometric titration show an increasing tendency when exposed to blue light. Dry weight and hypocotyl length were not considerably impacted by light treatment. These results suggest that blue light duration is important for boosting antioxidant capacity without sacrificing development. This discovery offers a workable method for enhancing the functional quality of mung bean sprouts for controlled-environment agriculture systems and functional food development.